DETERMINING FACTORS IN THE SEXUAL DIVISION OF LABOR IN THE COSTA RICAN TEXTILE INDUSTRY (1960-1980) - Mérienne, Florence (2020)
The following article aims to identify the determining factors in the sexual division of labor in the Costa Rican textile industry, which was strongly feminized between 1960 and 1980, a time of boom in textile production in this country. The analysis of primary and diverse sources revealed the diversity of the factors and actors involved. The investigation is based on the examination of the worksheets of several companies in the textile sector, of files for union persecution, of journalistic sources, and of the National Professional Learning Institute. Interviews with women workers and employers and literature were also used to reconstruct the sociocultural context. From this research, it appears that, even in a context of labor shortages in the Costa Rican textile industry, employers did not renounce to their gender vision and continue to organize work around the gender category. Legal norms, family models, and unions also inherit this gender vision and in turn contribute to perpetuating this sexual division of labor. Patriarchy and capitalism mutually nurtured each other in this process, resulting in a subordinate place in the production process for women, which translates into strong wage inequalities to the detriment of women workers. Although feminist organizations exist to question this vision, they are unable to transform their demands into a collective movement of national importance.